Teori Ketertarikan Byrne dan Griffit: Dampak Gadget pada Dinamika Interaksi Manusia Modern - Neti Saekoko; Andrian Wira Syahputra (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Doìnn Byrneì and William Griffit deìveìloìpeìd theì Inteìrpeìrsoìnal Attractioìn Theìoìry which highlights that similarity oìf attitudeìs is an impoìrtant factoìr in foìrming attractioìn beìtweìeìn individuals. Inteìractioìn is a reìlatioìnship beìtweìeìn twoì oìr moìreì peìoìpleì in which theì actioìns oìf oìneì peìrsoìn impact oìr changeì theì actioìns oìf anoìtheìr peìrsoìn. But with theì deìveìloìpmeìnt oìf digital teìchnoìloìgy such as theì inteìrneìt, soìcial meìdia and moìbileì deìviceìs, humans can noìw acceìss infoìrmatioìn and coìmmunicateì moìreì wideìly than beìfoìreì. This digital eìra has proìfoìundly changeìd theì way humans inteìract. Aim: Toì undeìrstand Byrneì and Griffith's theìoìry oìf inteìreìst in theì coìnteìxt oìf gadgeìt useì and theì influeìnceì oìf gadgeìts oìn varioìus aspeìcts oìf human inteìractioìn. Theì library reìseìarch meìthoìd is theì approìach useìd in this reìseìarch. This liteìratureì study useìs a deìscriptiveì analytical meìthoìd that utilizeìs varioìus reìseìarch toì suppoìrt theì analysis. Theì reìlatioìnship beìtweìeìn theì theìoìry oìf attractioìn accoìrding toì Doìnn Byrneì and William Griffit and theì useì oìf gadgeìts can beì eìxplaineìd throìugh seìveìral aspeìcts that shoìw hoìw teìchnoìloìgy influeìnceìs soìcial inteìractioìn and attractioìn beìtweìeìn individuals, which includeì Similarity, Proìximity, Poìsitiveì Soìcial Inteìractioìn, and Seìlf-Discloìsureì (Seìlf-Discloìsureì).